The appearance of sport as a travel motivation in traveling habits - Jordan TÜTÜNKOV-HRISZTOV; Anetta MÜLLER; Anikó MOLNÁR (Editura Universităţii din Oradea, 2020)
Traveling habits and tourism motivations are constantly changing and re-shaping. Because of this reason their examination is indispensable for the tourism industry, as the response to these changes is one of the defining elements of competitiveness and product innovation. In our research, we examined the traveling habits of young workers (average age=29,1 yrs, sd=24,00) in the context of destination choice and sport tourism motivations (N=1182). The survey found that the most popular destination was the European continent, with 71.5% of respondents choosing an EU country and 7.5% choosing a non-EU but European destination. 9.3% of the respondents have chosen only domestic (Hungarian) destination for their holiday in the past 2 years. The results show that only 36.3% of the respondents have taken part in a holiday without sport purposes, while the majority of them (63.7%) have taken part in a sport holiday with some frequency in the last 2 years. There was a difference regarding gender, with significantly more men reporting that they took part in sporting holidays than women (P=0.000). The most typical sporting activities of these types of holidays were swimming and water sports (22.2%), cycling (19.4%) and hiking (11.6%). In tourism product development, the development of leisure sports is of great importance, as it provides the health, entertainment and active recreation that guests demand, thus influencing the choice of destination.